ESSAY AS A TOOL FOR ASSESSMENT IN INTEGRATED FRENCH LANGUAGE EDUCATION - Tatyana G. Rakhmatulaeva (Russian Journal of Education and Psychology)
Background. Teaching French, just like any other foreign language, is inherently a comprehensive process. This comprehensive approach relies on a multifaceted methodology and a variety of teaching methods and tools. Each stage of foreign language instruction is built upon specific pedagogical techniques and a set of established rules.